2017
DOI: 10.1186/s13722-017-0079-8
|View full text |Cite
|
Sign up to set email alerts
|

Rethinking alcohol interventions in health care: a thematic meeting of the International Network on Brief Interventions for Alcohol & Other Drugs (INEBRIA)

Abstract: In 2016, the International Network on Brief Interventions for Alcohol & Other Drugs convened a meeting titled “Rethinking alcohol interventions in health care”. The aims of the meeting were to synthesize recent evidence about screening and brief intervention and to set directions for research, practice, and policy in light of this evidence. Screening and brief intervention is efficacious in reducing self-reported alcohol consumption for some with unhealthy alcohol use, but there are gaps in evidence for its ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
46
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(51 citation statements)
references
References 126 publications
(140 reference statements)
2
46
0
3
Order By: Relevance
“…Despite the significant barriers to screening patients for AOD problems (e.g. time constraints, attitudes toward substance use, uncertainty about how to assist, concerns about offending patients and disrupting rapport) , the patient consultation can provide a critical opportunity to intervene—if only to assertively link to AOD treatment services—with potential to reduce problem substance use, re‐presentation and health‐care costs.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the significant barriers to screening patients for AOD problems (e.g. time constraints, attitudes toward substance use, uncertainty about how to assist, concerns about offending patients and disrupting rapport) , the patient consultation can provide a critical opportunity to intervene—if only to assertively link to AOD treatment services—with potential to reduce problem substance use, re‐presentation and health‐care costs.…”
Section: Discussionmentioning
confidence: 99%
“…The findings show the potential impact of training on screening and brief interventions on attitudes of professionals outside the health area, since this universal tool can be used in different contexts (28) , cooperate with the understanding of how and in what contexts these strategies can work and what their real effectiveness is, which is a gap raised in the scientific literature (39) . In a previous study, actions to prevent the use of substances were mentioned as more effective when implemented by teachers than those offered by specialists (15) .…”
Section: Contributions To the Area Of Nursing Health Or Public Policymentioning
confidence: 86%
“…[4][5][6][7][8][9][10][11] However, there has been recent debate concerning the validity of this effectiveness evidence. 12,13 Most trials use self-reported alcohol consumption as their primary outcome measure rather than alcohol-related morbidity or mortality problems, and such self-reported outcomes may be subject to social desirability bias or other research participation effects. 14,15 Furthermore, the active ingredients of SBI have yet to be determined.…”
Section: Introductionmentioning
confidence: 99%